(untitled) (Global Journal of Science Frontier Research, 2019)
Modern studies found that our sun has maximal anti-vortices throw spinning energy balls and after a loop trajectory nearby back. Modern studies also found that passes at certain distance from a star, it causes tidal waves in it. near-by heavy Black Hole would pull a energy out. The tidal waves created by the Black Hole would balls from the star and the Black Ho since the Black Hole is distant and moving fast, it Left behind, they would start orbiting the star, while gradually cooling down until planets. This scenario fully agrees with ancient orbiting a star were born by the star and fathered by a Black Hole. knowledge on stars’ activity and the makes full sense.